2008
DOI: 10.1038/sj.bjc.6604340
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression and altered glycosylation of MUC1 in malignant mesothelioma

Abstract: Current interest in the MUC1/EMA mucin relates to its role in malignancy, and its potential as a therapeutic target. MUC1/EMA expression has been observed in the majority of epithelioid mesotheliomas. However, little is known of the characteristics of MUC1/ EMA in mesothelioma. Herein, we studied the cell surface and soluble expression of the MUC1/EMA glycoprotein, and determined the mRNA and genomic expression profiles in mesothelioma. We found that the anti-MUC1 antibody, E29, was the most diagnostically use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 30 publications
(24 reference statements)
2
22
0
Order By: Relevance
“…Our study suggests that cross-presentation of membrane-localized tumor antigens might represent a more complex system involving both LNresident and migratory DC subsets. This is important for tumor because in humans, several membrane associated tumor molecules have been shown to be antigenic, including gp100, tyrosinase, MUC-1 and carcinoembryonic antigen in melanoma, mesothelioma, and ovarian cancer, respectively [36][37][38]. Importantly, CD8 1 T cells specific for membrane-associated tumor antigens can be detected within sentinel LN and circulating in peripheral blood [39,40].…”
mentioning
confidence: 99%
“…Our study suggests that cross-presentation of membrane-localized tumor antigens might represent a more complex system involving both LNresident and migratory DC subsets. This is important for tumor because in humans, several membrane associated tumor molecules have been shown to be antigenic, including gp100, tyrosinase, MUC-1 and carcinoembryonic antigen in melanoma, mesothelioma, and ovarian cancer, respectively [36][37][38]. Importantly, CD8 1 T cells specific for membrane-associated tumor antigens can be detected within sentinel LN and circulating in peripheral blood [39,40].…”
mentioning
confidence: 99%
“…It is overexpressed in the majority of epithelioid MM in an altered glycosylation form (Creaney et al, 2008). While it has been shown that Muc-1 + MM cells are subject to CTL-mediated killing in vitro (Roulois et al, 2011), there are currently no Muc-1 targeted therapies under development for MM patients.…”
Section: Tumour-associated Antigens In MMmentioning
confidence: 99%
“…To date, it is known that MUC1 is overexpressed by MPM cells compared with normal mesothelioma cells [23]. Thus, MUC1 could represent an attractive TAA to target CTL responses against MPM.…”
Section: Alignant Pleural Mesothelioma (Mpm)mentioning
confidence: 99%